2019
DOI: 10.1634/theoncologist.2018-0468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Morphine on Dyspnea in Patients with Cancer: Response Rate, Predictive Factors, and Clinically Meaningful Change (CJLSG1101)

Abstract: Background Although the efficacy of parenteral morphine for alleviating dyspnea has been previously demonstrated in several studies, little is known regarding the efficacy of oral morphine for dyspnea among patients with cancer, including its response rate and predictive factors of effectiveness. Therefore, the aim of this study was to clarify the effectiveness of oral morphine on dyspnea in patients with cancer and elucidate the predictive factors of its effectiveness. Subjects, Materials, and Methods In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
8
1
Order By: Relevance
“…1,6 In addition, other effects of opioids may influence these results, that is, a possible reduction of respiratory rate improving tachypnea or respiratory effort, and an antitussive effect against dry cough. [16][17][18] However, a previous study has shown that opioid treatment neither causes a decrease in respiratory rate nor the effectiveness of opioids for treating patients with tachypnea. 19 Good PS may be selected for because dyspnea worsens in the terminal phase, when PS also declines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,6 In addition, other effects of opioids may influence these results, that is, a possible reduction of respiratory rate improving tachypnea or respiratory effort, and an antitussive effect against dry cough. [16][17][18] However, a previous study has shown that opioid treatment neither causes a decrease in respiratory rate nor the effectiveness of opioids for treating patients with tachypnea. 19 Good PS may be selected for because dyspnea worsens in the terminal phase, when PS also declines.…”
Section: Discussionmentioning
confidence: 99%
“…As no preexisting questionnaires matched our specific requirements, we developed a novel ad hoc questionnaire based on a literature review and discussion among the investigators. 1,2,[8][9][10][11][12][13][14][15][16] We described a hypothetical scenario of an adult ambulatory cancer patient with an expected survival of more than several months and a dyspnea score of 2 or 3 on the modified Medical Research Council Scale. For this hypothetical case, we inquired about the physician-perceived predictive factors for the effectiveness of drugs (opioids, benzodiazepines, and corticosteroids) in treating cancer dyspnea.…”
Section: Measurementsmentioning
confidence: 99%
“…Although STAS is not a subjective patient-reported outcome scale, its usefulness should be emphasized when considering the condition of patients in palliative care settings who might be delirious or in a drowsy state. Regarding the observation period required for symptom control, although effects of opioids against dyspnea can be evaluated within some hours to 2 days 40 , 41 , 14 days are necessary for opioid rotation against cancer pain treatment 42 . A 2-week period is also applied in some studies evaluating transitional changes of anxiety 43 , 44 .…”
Section: Methodsmentioning
confidence: 99%
“…Clinically these instruments have been used to describe breathlessness severity as a characteristic of cohorts (CDS [35]), differences between groups (D-12: frailty classifications in people with COPD [37]) and to identify changes in breathless sensation over time (D-12: across 3 months following admission to hospital for acute exacerbation of COPD with greater changes at each time point for physical subdomains (sensory qualities) versus affective subdomains [25 && ]). There are an increasing number of studies including multidimensional instruments to assess the impact of interventions on the sensation of breathlessness (MDP: before and 1 month after initiation of noninvasive ventilation in people living with ALS with chronic respiratory failure [33 && ]; pulmonary rehabilitation with and without inspiratory muscle training in people with severe/very severe COPD [38]; D-12: cognitive behavioural therapy for people with severe asthma and anxiety/ depression [30 && ]; CDS: oral morphine for cancerrelated breathlessness [39]).…”
Section: Multidimensional Instruments Developed For Adults Capable Of...mentioning
confidence: 99%
“…Pulm HT [31] ILD [32] Lung cancer [34] Y Y English [16], French [28], Portuguese [26], Italian [27], Swedish [36] Cancer Dyspnoea Scale [18] Y Y Y 1 2 Ordinal 1-5 Advanced lung cancer [18] Advanced lung cancer [22,23] Advanced cancer [21,35,39] Y Y Japanese [18], English [18], Swedish [23], Vietnamese [22], Hindi [21], Marathi [21] Dyspnea-ALS-scale Asthma, CF, healthy (8-18 years) [58] Histamine challenge [59] Exertional dyspnoea ( Dyspnoea-12 [16] Multidimensional Dyspnea Profile [17] Cancer Dyspnea scale (CDS) [18] Dyspnea-ALSscale [14] a None (0) Mild ( 1 sensations assessed by the MDP have been reported to be similar between aerosolized furosemide and saline [41…”
mentioning
confidence: 99%